Warehousing and inventory management activities at Musa - Santos, Catarina Luís da Silva (2019)
This project is developed under logistics and supply chain scope. It has been an evolving subject and it plays an important role in corporate business nowadays. In between all the topics this theme integrates, warehousing and inventory management are seen as critical activities. Inventory management is a fundamental part of the logistics management process due to the costs saving it leads to when having a well implemented structure. Warehousing management is an essential part of every logistics chain since it bridges the producer to the customer, due to its vital role in providing a desired level of customer service at the lowest possible total costs. Thus, this project is about warehousing and inventory management activities in a Portuguese craft beer company named MUSA. This is a sector that has been developing in Portugal in the last years. Many new players have entered the market recently and MUSA is between them. It is hence meaningful to contribute to the efficiency increasing of the company in such a competitive environment in order to be a step ahead of the market. Therefore, the goal was to make it possible in the management of these activities of warehousing and inventory management at MUSA. In order to provide value-added suggestions, information about the current management of these activities was collected. Considering that there are no proper inventory policies defined to each product, one of the main goals was to work on this settlement. Based on this information appropriate methods were applied. The models used for inventory policies were the continuous and periodic stochastic review models. For SKU classification in terms of importance level, the ABC analysis was performed. Results show that efficiency could be improved through the adoption of the right stock management policy since it provides a notion of the associated costs and hence capital could be allocated to other investments. The products allocation also allows to get visibility for future investment decisions.